An Enhancement of Least Significant BIT (LSB) Algorithm Applied in image Steganography - Alyanna Dawn S. Baldueza and Charmaine Beth L. Salcedo. 4 0 16; 5 (2015)
ABSTRACT: Steganography means the process of hiding information by embedding messages within an image. It used to increase the security of messages sent over the internet. The Least Significant Bit Algorithm applied in Steganography may have drawbacks despite being the most commonly used and simplest technique. The algorithm does not support all image formats on the Stego Image (output) and saves with a very large file size that may cause suspicion. Also, the Stego images modified by the algorithm are easily attacked by using Steganalysis. Steganalysis is the process of detecting steganography by looking at variances between bit patterns and unusually large file sizes. The proponents take these reasons to enhance and improve the said algorithm. For the first problem and objective, the enhanced algorithm was modified to add the most commonly used image formats in the list. For the second problem and objective, the researchers improved the process that deals on placing the bits of data inside the image. Instead of placing them in sequence which is the process used in the existing algorithm, the enhanced algorithm realigns the bits of data to reduce steganalysis attacks and suspicions. For the third problem and objective, the researchers added a compression process on saving the stego image wherein the file size will be the same as the original image. A simulator that used the existing algorithm and the developed image steganography application that used the enhanced algorithm were compared. For further enhancement of the algorithm, researchers recommend to consider other digital formats such as videos/audios and to secure other attacks on steganography.
Undergraduate Thesis (BSCS major in Computer Science) Pamantasan ng Lungsod ng Maynila, 2015.
Keywords: 2 -- 0; 6; 20; 20; 2